Photosynthesis, water use, and biomass allocation of princess tree (paulownia tomentosa) and tulip poplar (liriodendron tulipifera) first year seedlings across light and prescribed fire conditions - Dinkins, Hannah E. (2021)
Forest communities experience disturbances, such as fire and canopy removal, which create light gradients and microclimates that affect establishment, carbon gain, and height of native and invasive pioneer tree species that flourish in open or full sun areas. To test the hypothesis that the invasive tree Paulownia tomentosa (henceforth PATO, princess tree) has a stronger positive response to post-disturbance microclimates than native Liriodendron tulipifera (henceforth LITU, tulip poplar), I compared photosynthesis, biomass, and allometry of first-year seedlings of both species in a field experiment. The field study had a split-plot experimental design with plots distributed in two rows across forest light treatments (open, edge, canopy) and either burned or unburned treatments. Environmental variables (relative humidity, temperature, soil temperature, soil moisture), soil nutrients (nitrogen, phosphorus, and potassium (N, P, K)), gas exchange (transpiration, photosynthesis, and stomatal conductance), and allometry (number of branches, plant height, number of leaves, plant width, and stem width) measurements were made. Additional allometric measurements (leaf mass, average internode length per plant, root collar diameter, total plant biomass, average root length, number of lateral roots), along with tissue carbon: nitrogen ratios, were taken at the end of the growing season. Air temperature, soil moisture content, and soil temperature varied among light treatments. The interaction between row and light treatments also differed in microclimates in the field study. The only significant difference detected for photosynthetic rates and stomatal conductance occurred between rows A and B; net photosynthesis and stomatal conductance of both species were higher in row B. Neither species differed in water use efficiency (WUE) between burned or unburned treatments or among light treatments. Neither mean leaf area, specific leaf area (SLA), nor root length differed among treatments. All other allometric measurements differed significantly between the species and among light treatments. PATO was larger in size across all allometric measurements. Overall, the allometric results suggest PATO had greater growth and was larger across all microclimates of burned and unburned soil conditions and light treatments compared to LITU. The C:N ratios revealed that PATO had more carbon in their roots compared to LITU, while LITU invested more carbon into their leaves than PATO. LITU had more nitrogen in its roots, leaves, and stems than PATO. Future research should be conducted to compare PATO with other native species such as yellow birch (Betula alleghaniensis), red maple and sugar maple (Acer rubrum and Acer saccharum), and American beech (Fagus americana). In addition to comparing PATO’s photosynthetic rates, biomass accumulation, and success of establishment across different microclimates among different ecosystem communities, PATO’s ability to obtain nutrients and association with arbuscular mycorrhizal fungi, which are the fungi that benefits plants by obtaining nutrients needed for growth and development, should be investigated due to the nutrient change found within the nutrient soil samples. Overall, PATO’s ability to gain rapid height growth and leaf mass, and allocate its resources, especially in full sun, to growth and establishment suggest that PATO will continue to increase on the landscape in Southeastern forests, perhaps at the expense of LITU.